2016
DOI: 10.17645/mac.v4i4.576
|View full text |Cite
|
Sign up to set email alerts
|

Hazy Boundaries: Virtual Communities and Research Ethics

Abstract: This paper examines ethical issues specific to research into virtual communities. Drawing on an empirical case with online forums of education experts, we identify the following key issues: publicity versus privacy of the community; the definition of human subjects research; participant recruitment; informed consent; and ethical questions associated with observing virtual communities, and with reporting and disseminating research results. We maintain that different research cultures in different countries can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
10
0
4
Order By: Relevance
“…These findings are in line with previous studies, whereby the limited resources of the CSO cause long delays and even deter researchers from submitting research plans for ethical approval or encourage them to alter their research question (Hazzan et al, 2018). In other cases, researchers simply recruit teachers (i.e., participants) through social media, without considering the related ethical problems (Kantanen & Manninen, 2016). Although some policy changes have been introduced by the CSO, specifically delegating school principals to ethically approve studies, they have not yet received adequate support from researchers.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with previous studies, whereby the limited resources of the CSO cause long delays and even deter researchers from submitting research plans for ethical approval or encourage them to alter their research question (Hazzan et al, 2018). In other cases, researchers simply recruit teachers (i.e., participants) through social media, without considering the related ethical problems (Kantanen & Manninen, 2016). Although some policy changes have been introduced by the CSO, specifically delegating school principals to ethically approve studies, they have not yet received adequate support from researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Este daño puede ser mental, económico o social, además de ocurrir en distintos momentos de la investigación, incluidas la recolección de los datos y la publicación de los resultados (Kantanen & Manninen, 2016). En su trabajo, Rosenberg (2010) también destaca la importancia de no causar daño a los y las participantes y a la sociedad en general, pero menciona otro objetivo, en el que nos centraremos más adelante: comprender dónde está el límite entre lo privado y lo público ayuda, precisamente, a no herir a quienes analicemos.…”
Section: Marco Teóricounclassified
“…Algo que puede ayudar a esclarecer estas interrogantes sobre el consentimiento es considerar la metodología que se emplee. El consentimiento informado es requerido siempre y cuando la persona que investiga realice entrevistas (Kantanen & Manninen, 2016), por lo que una aproximación que solo se base en el material escrito por los usuarios y usuarias podría no requerir solicitar esta aprobación. Willis (2017) propone dos condiciones que permitirían prescindir del consentimiento informado: si los datos son públicos y si son solamente textuales.…”
Section: Consentimiento Informadounclassified
See 1 more Smart Citation
“…Both the Finnish National Board on Research Integrity TENK (n.d.) and Sveningsson's model (as cited in Östman & Turtiainen, 2016) have been used to determine the sensitivity of the personal data used. Given that Ersson's video was live streamed and subsequently publicly posted, I concluded that it was intended for public use (Kantanen & Manninen, 2016). I exercised caution, however, with the comments that were posted to the video.…”
Section: Research Ethicsmentioning
confidence: 99%